CONSERVATIVE ORTHODONTIC TREATMENT IN A CASE WITH SEVERE DENTAL CROWDING - Loredana Golovcencu; Daniela Anistoroaei; Alina Claudia Sodor; Iulia Catalina Saveanu; Georgeta Zegan (Romanian Society of Oral Rehabilitation, 2019)
Non extraction orthodontic treatment should be the best choice for both practitioners and patients when possible. That's why in the last decades people are concerned more and more in developing new techniques for solving orthodontic problems without dental extractions . In our paper we present an adolescent case with severe dental crowding with two stage orthodontic treatment; in the first stage we used pedex appliance for distal movement of upper molars and correction of transverse discrepancy, followed by the second stage with fixed orthodontic appliance. The patient presented ectopic upper canines and class II malocclusion. At the end of the treatment our patient presented correct dental alignment, functional and stable occlusion, good profile, nice smile and improvement of the facial esthetics.